In planta Female Flower Agroinfiltration Alters the Cannabinoid Composition in Industrial Hemp (Cannabis sativa L.) - Deguchi, Michihito; Dhir, Seema; Potlakayala, Shobha; Dhir, Sarwan; Curtis, Wayne R.; Rudrabhatla, Sairam (Frontiers in Plant Science, 2022)
Industrial hemp is a diploid (2n = 20), dioecious plant, and an essential source of various phytochemical productions. More than 540 phytochemicals have been described, some of which proved helpful in the remedial treatment of human diseases. Therefore, further study of hemp phytochemicals in medicine is highly anticipated. Previously, we developed the vacuum agroinfiltration method, which allows the transient gene expression in hemp tissues including female flowers, where cannabinoids are produced and accumulated. In this study, we attempted to alter the composition of total CBD and THC. The RT-PCR and sanger sequence identified eleven copies of the CBDAS gene, two copies of the THCAS gene, and one CBCAS gene. Binary vectors were constructed to overexpress the CBDAS gene and silence the THCAS gene via RNA interference. The Transcript level of the CBDAS gene was increased by more than ten times than the plants used as a control, which led to a 54% higher total CBD content. The silencing of the THCAS gene led to downregulation of the THCAS gene, with an 80% reduction in transcript levels, and total THC content was reduced to 43% compared with mock plant. These results suggest that hemp vacuum infiltration is highly effective for metabolic engineering of cannabinoids in hemp.